The Annual Report of the Society for Financial Studies for 2019–2020 - Chan, Kalok; Ellul, Andrew; Goldstein, Itay; Holden, Craig; Piazzesi, Monika; Pontiff, Jeffrey (The Review of Asset Pricing Studies, 2021)
The Society for Financial Society (SFS) is a global, nonprofit academic society in finance. It owns and runs three academic journals: (1) the Review of Asset Pricing Studies, (2) the Review of Corporate Finance Studies, and (3) the Review of Financial Studies. It also organizes two annual academic conferences: (1) the SFS Cavalcade Asia-Pacific and (2) the SFS Cavalcade North America. It also runs several smaller, specialized conferences and financially supports and co-sponsors other independent conferences. Its governing board is the SFS Council. This annual report provides an overview of SFS activities during 2019-2020, including all three journals, both Cavalcade conferences, and the SFS financial and policy report. The purpose of this annual report is to share this information more broadly with SFS members and friends and to create a permanent record for the long-run (i.e., institutional memory). 2020 was a busy year for the Review of Asset Pricing Studies (RAPS). We renewed Associate Editors Clemens Sialm and Dimitri Vayanos. We added a special COVID-19 issue. This issue contained 11 papers and an introduction by Lars Peter Hansen. We expect that these papers will provide a foundation for future finance and economics research that is related to COVID.